2003
DOI: 10.1080/13550280390194109
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus-Associated Dementia: An Evolving Disease

Abstract: This article reviews the changing epidemiology of HIV-associated dementia, current concepts of the different patterns of dementia under the influence of highly active antiretroviral therapy, and reviews therapeutic aspects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
276
0
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 361 publications
(284 citation statements)
references
References 127 publications
3
276
0
5
Order By: Relevance
“…Recent concern about the consequences of HAD has emerged with the increasing resistance to antiretroviral drugs. With introduction of HAART, therefore, the patients on HAART with a slowly progressive dementia and incomplete virological control have been proposed (McArthur et al, 2003). Recently, Brenchley et al reported that plasma LPS levels are still higher in chronic HIV-infected patients with HAART than in the uninfected (Brenchley et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Recent concern about the consequences of HAD has emerged with the increasing resistance to antiretroviral drugs. With introduction of HAART, therefore, the patients on HAART with a slowly progressive dementia and incomplete virological control have been proposed (McArthur et al, 2003). Recently, Brenchley et al reported that plasma LPS levels are still higher in chronic HIV-infected patients with HAART than in the uninfected (Brenchley et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…With increased life expectancy, the prevalence of HIV-associated cognitive and neurological impairment is actually rising despite highly active antiretroviral therapy. 5,6 A number of therapeutic agents have been tried to target pathological sequelae of HIV neurological infection, ranging from the pain associated with peripheral neuropathology to neuron dysfunction and death, but few have been approved for clinical use. Thus, it is necessary to explore alternative strategies for treating HIV-associated neurological diseases.…”
Section: Human Immunodeficiency Virus (Hiv)-1 Tat Protein Ismentioning
confidence: 99%
“…Graus menores de dano cognitivo, motor e funcional, na qual não são suficientes para o diagnóstico de demência é chamado transtorno cognitivo-motor menor associado-HIV e nem sempre pacientes com estes transtornos evoluem para franca demência 5 .…”
Section: Diagnóstico Das Alterações Cognitivas Da Aidsunclassified
“…Portanto é importante reconhecer precocemente danos sutis, já que, em alguns casos, podem significativamente melhorar a chance de reversão da demência com HAART 5 , melhorar a qualidade de vida com tratamentos adicionais 46 e mesmo possibilitar a monitorização da aderência do paciente à medicação. Além do fato de poder melhorar a orientação para os familiares sobre as alterações comportamentais e cognitivas do paciente.…”
Section: Diagnóstico Das Alterações Cognitivas Da Aidsunclassified
See 1 more Smart Citation